PROBLEMS OF FORMATION OF SOCIO-ECONOMIC INSTITUTE OF MANAGEMENT IN RUSSIA - N. V. Lyasnikov; M. N. Dudin (Модернизация, инновация, развитие, 2016)
The dynamic socio-economic development of Russia, the long-term competitiveness in the global economy involves the formation of a new socio-economic institute of management – an active subject of modern innovative economy.